Pharmacoeconomics and Utilization of Intravenous Proton Pump Inhibitors in a Tertiary Care Hospital - Prerana Kadam; Smita Tiwari; Bharti Daswani; Ajay Taware; Rajesh Hiray (Research Center for Rational Use of Drugs (RCRUD), 2022)
Background: Proton pump inhibitors (PPIs) are one of the most frequently prescribed class of drugs worldwide contributing to the increase in economic burden on the healthcare system. To study the utilization of intravenous proton-pump-inhibitors (PPIs) according to its indications, comorbidities and related pharmacoeconomics in a tertiary care teaching hospital Methods: A prospective-observational study was conducted over 3 months. Case-records of 300 indoor patients were reviewed for IV (intravenous) pantoprazole prescription, as it was the only PPI available at the hospital in IV as well as oral formulations and relevant data was procured. Results: Amongst 300 patient records, 72% were males whereas 28% were females and mean age was 41.18 years (S.D. ± 15.91). 37.33% of the patients were prescribed PPIs for Stress ulcer prophylaxis and 62.66% for non-stress ulcer prophylaxis. 62.66% patients were prescribed IV PPIs inappropriately and 74% were found to be potential candidates for oral pantoprazole therapy without affecting patient outcomes. Utilisation of PPIs was found to be 0.87 defined daily dose (DDD)/100 bed days. The cost of administration for intravenous pantoprazole therapy per patient per day accounted to INR 64.34 and that for oral formulation of the same summed up to INR 1.36. The percentage reduction in the cost of administration of PPI therapy per patient in potential candidates for oral PPI therapy was found to be 97.8%. Antimicrobials (36%) were the most common drugs prescribed concomitantly followed by antiemetics (25%). Conclusion: Subtle changes like shifting the patient to oral formulations when clinically permissible can make a significant positive contribution in resource limited settings without negatively impacting patient outcomes. This will effectively reduce the economic burden on the patients and the healthcare system which is of utmost importance in a resource limited setting like tertiary care hospitals.